Часовi характеристики пiслясвiтiння у штучному опалi - Vasnetsov, M. V.; Bazhenov, V. Yu.; Ponevchinsky, V. V.; Plutenko, D. O.; Kudryavtseva, A. D.; Tcherniega, N. V. (Publishing house "Academperiodika", 2019)
We report the results of an experimental study of the temporal response of the artificial opal luminescence excited by UV pulses from a nitrogen laser at room temperature, liquid-nitrogen temperature, and in the intermediate range. While the response time does not exceed 15 ns at room temperature, the afterglow at liquid-nitrogen temperature was detected with a decay time of about 700 ms. We have revealed that the afterglow appears suddenly with just millisecond-range duration at a definite temperature of 130±5 K. The temperature dependence of the afterglow is of importance for the explanation of surprising effects of the stimulated emission in a single nano-sized SiO2 globule and the second harmonic generation in the material at liquid-nitrogen temperature.